2018
DOI: 10.1002/jcop.22142
|View full text |Cite
|
Sign up to set email alerts
|

The sleep environment and its association with externalizing behaviors in a sample of low‐income adolescents

Abstract: This study examined the sleep environment and its association with externalizing problems in adolescents attending an alternative high school. Participants included 114 students (56% female, 91% Black, mean age = 18.03, standard deviation [SD] = 1.49) from an alternative high school in a southeastern city. Most participants reported sleeping in a bed (83%) and at their house (72%) for 7 nights in the past week. Participants reported an average of 2.34 (SD = 1.86) past‐week ambient sleep disruptions. Sleeping f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
(73 reference statements)
1
1
0
Order By: Relevance
“…Just as described by the young people interviewed here, quantitative research has found sleep environment factors to be related to poorer sleep for adolescents, including noise inside and outside of the home, 45 including for adolescents attending an alternative school. 63 In line with what the young people interviewed described, a large amount of technology use in the daytime and night time is typical for adolescents, and use of technology at night time is associated with poorer sleep and daytime functioning. [14][15][16]64,65 Mobile phone use and social networking engagement at night time have been associated with poorer wellbeing through the mediating variable of sleep disruption.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Just as described by the young people interviewed here, quantitative research has found sleep environment factors to be related to poorer sleep for adolescents, including noise inside and outside of the home, 45 including for adolescents attending an alternative school. 63 In line with what the young people interviewed described, a large amount of technology use in the daytime and night time is typical for adolescents, and use of technology at night time is associated with poorer sleep and daytime functioning. [14][15][16]64,65 Mobile phone use and social networking engagement at night time have been associated with poorer wellbeing through the mediating variable of sleep disruption.…”
Section: Discussionsupporting
confidence: 57%
“…Just as described by the young people interviewed here, quantitative research has found sleep environment factors to be related to poorer sleep for adolescents, including noise inside and outside of the home, 45 including for adolescents attending an alternative school. 63 …”
Section: Discussionmentioning
confidence: 99%